Pengaruh Event Marketing “Social Media Expert Series” Terhadap Purchase Intention Yang Dimediasi Oleh Brand Awareness Pada Produk Practiclass By Ngalup.co - Saifullah, Haris; Asnawi, Nur (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The research was conducted with the aim of analyzing the influence of the "Social Media Expert Series" marketing event on the purchase intention of PractiClass by Ngalup.co products with brand awareness as a mediation variable. The research was conducted by quantitative methods using a descriptive approach. In determining the sample, purposive sampling techniques were used and the sample size was determined using the slovin formula with a sample of 67 respondents. Partial Least Square is a type of data analysis method in this study assisted by Smart-PLS 4 software. The results showed that event marketing affects purchase intention, event marketing affects brand awareness, then brand awareness affects purchase intention, and finally brand awareness is able to mediate the influence of event marketing on purchase intention on PractiClass by Ngalup.co products.